Erythrocytosis incidence and thromboembolic risk in heart failure with reduced ejection fraction treated with SGLT2 inhibitors: a nationwide register-based cohort study - Abdullahi Ahmed Mohamed; Camilla Fuchs Andersen; Daniel Mølager Christensen; Lise Da Riis-Vestergaard; Milan Mohammad; Mariam Elmegaard; Casper Binding; Christian Torp-Pedersen; Tor Biering-Sørensen; Morten Lock Hansen; Lars Køber; Andreas Glenthøj; et al. (Cardiovascular Diabetology)
Abstract Background Sodium-glucose cotransporter-2 inhibitors (SGLT2i) increase haemoglobin and haematocrit levels, potentially causing secondary erythrocytosis—defined as a haemoglobin level above 16.5 g/dL in men and 16.0 g/dL in women—which is associated with an elevated thromboembolic risk. This study investigated the incidence of erythrocytosis and its association with thromboembolic events in patients with heart failure with reduced ejection fraction (HFrEF) treated with SGLT2i. Methods In this nationwide cohort study, we included 3138 patients with new-onset HFrEF who initiated SGLT2i treatment after diagnosis, and 3138 propensity score-matched untreated controls. Haemoglobin was measured at baseline and six-month follow-up. Erythrocytosis incidence at follow-up was assessed using Poisson regression. Cox models were used to evaluate the association between erythrocytosis and one-year risk of fatal and non-fatal thromboembolic events (myocardial infarction, stroke, pulmonary embolism, or deep venous thrombosis), stratified by SGLT2i treatment. Results Erythrocytosis developed in 207 patients (3.3%). Incidence was higher among SGLT2i-treated patients (109.5 vs. 26.8 per 1000 person-years), with an adjusted incidence rate ratio of 4.10 (95% CI 2.95–5.83). No significant association was observed between erythrocytosis and one-year thromboembolic risk in the total population (HR: 0.85 95% CI 0.44–1.65), even when stratified by SGLT2i-treated (HR: 0.81 95% CI 0.38–1.74) and untreated patients (HR: 0.75, 95% CI 0.19–3.05) (interaction P = 0.77). Conclusion Although erythrocytosis incidence was higher in SGLT2i-treated HFrEF patients, it was not associated with an increased one-year thromboembolic risk. Graphical Abstract